2020
DOI: 10.1007/s00464-020-07791-2
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of robotic-assisted versus open pancreatoduodenectomy for pancreatic ductal adenocarcinoma: a propensity score-matched analysis

Abstract: Background Robotic-assisted minimally invasive surgery is associated with worse oncologic outcomes for some but not other types of cancers. We conducted a propensity score-matched analysis to compare oncologic outcomes of robotic-assisted laparoscopic (RPD) vs. open pancreatoduodenectomy (OPD) for pancreatic ductal adenocarcinoma (PDAC). Methods Treatment-naïve PDAC patients undergoing either RPD or OPD at our hospital between January 2013 and December 2017 were included. Propensity score matching was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Regarding the effect of minimally invasive PD on DGE development, the findings are inconclusive. National registries [ 37 ] and meta-analyses [ 38 , 39 ] were not able to detect an effect, single-center studies showed different results ( 40 , 41 ). Robotic PD was introduced in our department several years ago, but because its use does not span the whole period, we did not include minimally invasive PD into our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of minimally invasive PD on DGE development, the findings are inconclusive. National registries [ 37 ] and meta-analyses [ 38 , 39 ] were not able to detect an effect, single-center studies showed different results ( 40 , 41 ). Robotic PD was introduced in our department several years ago, but because its use does not span the whole period, we did not include minimally invasive PD into our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…14 A recent study based on the National Cancer Database reported that median overall survival times of RAPD and open PD were 22.0 and 21.8 months, respectively, with a similar overall survival between the two groups (P = .755) 16 ; however, it did not limit possible confounding factors for survival, such as the number of retrieved lymph nodes (RAPD vs open PD, 22 ± 12 vs 17 ± 11, P < .001). Another study showed similar survival outcomes between RAPD and open PD using a PSM analysis 17 ; however, the number of retrieved lymph nodes was relatively small (RAPD, 11; IQR, 7-16 vs open PD, 11; IQR, 6-17; P = .622), less than the suggested ≥15 retrieved lymph nodes for curative-intent pancreatectomy to optimize operative benefits. 18 In our study, we performed subgroup stage-matched comparison for each disease entity, including PDAC, distal CBD cancer, AoV cancer, duodenal cancer, and malignant IPMN.…”
Section: F I G U R E 1 Comparison Of Overall Survival In Patients Wit...mentioning
confidence: 96%
“…Among the 16 included controlled studies about LPD and OPD for the treatment of pancreatic cancer, two were randomized controlled experiments (Palanivelu et al, 2017;Wang et al, 2021), and 14 were retrospective studies (Cho et al, 2009;Bao et al, 2014;Croome et al, 2014;Mendoza et al, 2015;Stauffer et al, 2017;Chapman et al, 2018;Kim et al, 2019;Tan et al, 2019;Choi et al, 2020;El Nakeeb et al, 2020;Han et al, 2020;Kwon et al, 2020;Weng et al, 2021;Zhang et al, 2022), involving a total of 4416 patients, including 1275 in the LPD group and 3141 in the OPD group. See Table 1 for literature characteristics, see Supplementary Table S2 and Supplementary Figures S1, S2 for the quality evaluation of the included studies.…”
Section: Basic Characteristics and Quality Evaluation Of The Included...mentioning
confidence: 99%
“…Among the included studies, a total of 13 articles (Cho et al, 2009;Bao et al, 2014;Croome et al, 2014;Mendoza et al, 2015;Palanivelu et al, 2017;Stauffer et al, 2017;Kim et al, 2019;Tan et al, 2019;Choi et al, 2020;El Nakeeb et al, 2020;Han et al, 2020;Wang et al, 2021;Weng et al, 2021) mentioned the index of operation time. Among them, 907 cases were part of the LPD group and 1355 cases were in the OPD group.…”
Section: Operation Timementioning
confidence: 99%